2013
DOI: 10.4161/auto.26398
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition suppresses pulmonary metastasis of HCC in mice via impairing anoikis resistance and colonization of HCC cells

Abstract: (2013) Autophagy inhibition suppresses pulmonary metastasis of HCC in mice via impairing anoikis resistance and colonization of HCC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(210 citation statements)
references
References 36 publications
5
203
0
2
Order By: Relevance
“…16 Furthermore, in mouse models of pulmonary metastasis of hepatocellular carcinoma cells, inhibition of autophagy has been shown to significantly decrease the incidence of pulmonary metastases in vivo. 17 Inhibition of autophagy via knockdown of autophagy related 12 (ATG12) in glioma cells does not affect cell viability, proliferation, or migration, but significantly reduces cellular invasion in a 3-dimensional (3D) organotypic model. Thus, autophagy may play a critical role in the benign-to-malignant transition that is central to the initiation of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, in mouse models of pulmonary metastasis of hepatocellular carcinoma cells, inhibition of autophagy has been shown to significantly decrease the incidence of pulmonary metastases in vivo. 17 Inhibition of autophagy via knockdown of autophagy related 12 (ATG12) in glioma cells does not affect cell viability, proliferation, or migration, but significantly reduces cellular invasion in a 3-dimensional (3D) organotypic model. Thus, autophagy may play a critical role in the benign-to-malignant transition that is central to the initiation of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that, once the tumor cells are present in the lung, autophagy is not essential for survival. An earlier study of hepatocellular carcinoma demonstrated that autophagy was required for lung colonization due to anoikis resistance; however, the authors also noted that autophagic activity was more apparent in early-stage lesions (Peng et al, 2013).…”
Section: Autophagy Inhibition Delays Early Metastatic Disease Discussionmentioning
confidence: 97%
“…Autophagy is induced in detached breast cancer epithelial cells and is necessary for their continued survival (Fung et al, 2008). In a model of hepatocellular carcinoma, autophagy inhibition did not alter invasion or migration, but could attenuate anchorageindependent growth (Peng et al, 2013). Additionally, autophagy levels appeared highest in early metastatic lesions, and autophagy was only necessary in the lung-colonization stage.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of HCC has been done conducted at the level of genes, ribonucleic acid (RNA), proteins, cells, and animals [10][11][12][13][14]. The resultant development of animal models and monitoring methods has improved the effectiveness of guidelines provided to researchers working with preclinical HCC models.…”
Section: Introductionmentioning
confidence: 99%